Implementation of The Amaliyah Tadris Program to Grow and Develop Pedagogical Competencies: Study of Sixth Grade Student Tarbiyatul Mu’allimien Al-Islamiyah in Al-Amien Islamic Boarding School - Billah, Mustaqim; Amani, Izzat (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
Teachers are a key factor in the quality of education and progress of the nation. A country that ignores teachers (Teachers must be role models for their students inside and outside the classroom) will find it difficult to progress, because the next generation will be determined by parents and teachers as well as the government. This has become the norm, but in practice it is difficult. The government is half-hearted in improving teachers and improving the quality of education in many ways. The poor quality of education in Indonesia cannot be resolved by changing the curriculum or changing the Minister or General Manager. The quality of education can only be answered by the quality of teachers. Professional teachers, guaranteed teacher quality. Without improving the quality of teachers, the quality of education will remain inadequate. Therefore, one of the efforts made by the Tarbiyatul Mu'allimien Al-Islamiyah Al-Amien Prenduan Islamic boarding school is to provide students, especially male students in class VI, with an activity called 'Amaliyah Tadris (teaching practice). This teaching practice activity is carried out by final class students (class VI or . This research methodology uses a qualitative approach. A research method that produces descriptive data resulting from collection using observation, interviews and documentation studies. Based on the analysis carried out by researchers during the research process, the results of this research are as follows: Implementation of the Amaliyah Tadris program in an effort to develop pedagogical competence can be done through planning learning, conceptualizing learning planning, implementing microteaching as an exercise in managing learning, basic skills for managing learning (teaching skills) , and evaluation as a form of teacher performance assessment. Meanwhile, the implications of the Amaliyah Tadris program include: Producing competent teacher cadres and as a selective function for teacher candidates at TMI al-Amien Prenduan Sumenep Madura.